Efektivitas Penggunaan Aplikasi E-Kinerja dalam Meningkatkan Kinerja Pegawai Negeri Sipil (PNS) di Badan Kepegawaian, Pendidikan, dan Pelatihan Daerah Kota Kupang - Anjelica Nareth Dami Ngara; Laurensius P. Sayrani; Jim Brand Kolianan; Mariayani O. Rene (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effectiveness of the e-Kinerja application in improving the performance of Civil Servants at the Regional Personnel, Education and Training Agency (BKPPD) of Kupang City. The research employed a qualitative approach with a descriptive research design. Informants were selected using purposive sampling, consisting of institutional leaders and employees who use the e-Kinerja application. Data were collected through observation, interviews, and documentation, and analyzed using qualitative data analysis techniques including data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation techniques. The effectiveness analysis referred to Sutrisno’s indicators, namely program understanding, target accuracy, timeliness, goal achievement, and real changes. The results indicate that the implementation of the e-Kinerja application in BKPPD Kupang City is relatively effective. The system has improved reporting discipline, transparency in performance evaluation, and facilitated monitoring of employee performance. However, several challenges remain, including limited digital literacy among employees, technological infrastructure constraints, and the tendency to focus on administrative aspects rather than substantive performance improvement. Therefore, strengthening socialization, improving digital literacy, and developing a more adaptive system are necessary to optimize the implementation of e-Kinerja in enhancing the quality of civil servant performance.